Temperature impact on dusty and cleaned photovoltaic module exposed in sub-Saharan outdoor conditions - Kata N'detigma; Soro Y. Moussa; Diouf Djicknoum; Darga Arouna; Maiga A. Seidou (EPJ Photovoltaics, 2018)
In this work, impacts of temperature and dust cleaning on photovoltaic module performance operating in sub-Saharan's climate are investigated. Two single junction technologies, monocrystalline and polycrystalline silicon, and one micromorph (amorphous/micrystalline) thin film silicon tandem technology are considered. We have recorded at the same time under real operating conditions, the module temperature and the current versus voltage characteristics of each module, and the local solar irradiation. All the measurements were performed with the outdoor monitoring and test facility located at Ouagadougou in Burkina Faso. The results show the drop of generated power of dusty modules for the same irradiation level. Between April and June (where temperatures are higher) a significant drop of output power is observed, despite a daily cleaning. Furthermore, performance losses are observed for all technologies compared to that under standard test conditions. However, the micromorph silicon tandem technology with low temperature sensitivity present the less losses in performance compared to the monocrystalline and the polycrystalline single junction modules, even if the modules are not cleaned.